Single-stage laparoscopic management for concomitant gallstones and common bile duct stones versus two stages using endoscopic retrograde cholangiopancreatography procedures - Aldardeer, Ahmed Abd El-Kahaar; Tag El-din Mohammed Sayed, Mohammed; El-Mageed, Magdy Khalil Abd; Redwan, Alaa Ahmed (International Surgery Journal, 2025)
Background: The optimal treatment for common bile duct (CBD) stones remains debated, with options including open or laparoscopic exploration, and endoscopic retrograde cholangiopancreatography (ERCP) before, during, or after laparoscopic cholecystectomy (LC). This study compared outcomes of one-stage (LECBD+LC) and two-stage (ERCP+LC) procedures for patients with gallstones and CBD stones, focusing on complications and patient satisfaction. Methods: A randomized retrospective and prospective study included 200 patients with gallstones and CBD stones. Patients were divided into group I (n=100), undergoing one-stage laparoscopic CBD exploration (transcystic or transcholedochal) plus LC, and group II (n=100), undergoing two-stage preoperative ERCP then LC. Outcomes included operative time, complications, hospital stay, residual stones, and patient satisfaction. Results: Mean age was 43.16±12.66 in group I and 41.52±9.44 in Group II, with no significant gender differences. Preoperative jaundice was present in 88 group I and 86 group II patients. Operative times, conversion rates, and complication rates were similar. The visual analogue scale (VAS) score at 24 hours was lower in group I but comparable at 3 days. Hospital stays were similar, with 3% residual stones in group I and 0% in group II. Patient satisfaction and mortality rates showed no significant differences. Conclusions: One-stage LCBDE with LC is equivalent to two-stage ERCP plus LC in terms of operative time, complications, hospital stay, residual stones, and patient satisfaction. Both approaches are effective, with no significant differences in outcomes.